Estratégias de marketing para fidelização da clientela - Waschburger, Francisco (2007)
The study whose theme is the marketing strategies for the fidelization of the clientele, had the objective to verify the degree of satisfaction of the clients with the quality of the relationship practiced in the women's clothing stores in Santa Rosa - RS. The methodology was a research involving strategical attributes of relationship: confidence, sympathy, friendship/kindness, recognition and emotional dimension dispensed to the clients of women's clothing stores in Santa Rosa - RS, with assertives that were analysed by the SERVQUAL method. That method measures tangible items, reliability, receptivity, safety and empathy, and in this study, it was used of relative subjects the dimensions trust, empathy, friendship and human warmth, recognition and emotional dimensions.The study allowed to conclude that the women become faithful to the companies from the relationships with managers and employees of them. The clients value the strategical attributes: confidence, sympathy, friendship and kindness, recognition and emotional dimensions in the relationships established with the companies. The companies that pay attention to these strategical attributes provide the satisfaction of the clients in the relationships and, consequently, the clients fidelization to the companies. The research realized with the clients of women's clothing stores in Santa Rosa, also allowed to conclude that the women's clothing companies are in an upward movement in the scale of quality in relationships, the general average of frequency of 3,37. This index indicates an upward movement to the agreement to the strategical attributes of relationship in focus. It is suggested that the managers notice the improvements required and mentioned by the clients, paying attention to the minimum and maximum degrees of disagreement and agreement in each assertive of the study, to rise the increasing of the satisfaction with the quality of relationships as a return for the action of the applicability of companies strategies.